The Critical Intervention Screen: A Novel Tool to Determine the Use of Lights and Sirens during the Transport of Trauma Patients. (21st June 2022) - Urban, Shane; Carmichael, Heather; Moe, Martin; Kramer, Andrea; Al-Azzawi, Omar; Dumond, Robbie; Wright, Angela; McIntyre, Robert; Velopulos, Catherine
Abstract: Objective: EMS use of lights and sirens has long been employed in EMS systems, despite an increased risk of motor vehicle collisions associated with their use. The specific aims of this study were to assess the current use of lights and sirens during the transport of trauma patients in a busy metropolitan area and to subsequently develop a novel tool, the Critical Intervention Screen, to aid EMS professionals tasked with making transport decisions in the presence of acute injury. Methods: This single-center, retrospective study included all patients transported to an academic Level One trauma center by ground ambulance from the scene of presumed or known injury. A subset of patients was identified as being most likely to benefit from shorter transport times if they received one of the following critical interventions within 20 minutes of emergency department arrival: intubation, thoracotomy, chest tube, blood products, central line, arterial line, REBOA, disposition to an operating room, or death. Stepwise logistic regression was employed for the development of the Critical Intervention Screen, with a subset of data retained for internal validation. Results: 1296 patients were available for analysis. Overall, 217 patients (16.7%) received a critical intervention, and 112 patients (8.6%) of those patients received a critical intervention within 20 minutes of emergency department arrival. At baseline, EMS use of lights and sirens was 91.1% sensitive and 80.3% specific for receiving a critical intervention. Stepwise logistic regression demonstrated that the need for assisted ventilation, GCS Motor < 6, and penetrating trauma to the trunk were the most predictive prehospital data for receiving at least one critical intervention. The Critical Intervention Screen, defined as having at least one of these risk factors in the prehospital setting, modestly increased sensitivity and specificity (96.4% and 87.9%, respectively) predicting the need for a critical intervention. Conclusion: These findings indicate that EMS are able to correctly identify high-acuity trauma patients, but at times employ L&S during the transport of patients with a low likelihood of receiving a time-sensitive intervention upon emergency department arrival. Therefore, the Critical Intervention Screen has the potential to reduce the use of lights and sirens and improve EMS safety.